Internet of Things for Monitoring Infusion Fluids in Intravenous Chemotherapy Patients: Literature Review - Herlin Ajiyanti; La Ode Abdul Rahman (Formosa Publisher, 2022)
Administration of intravenous chemotherapy drugs to cancer patients requires sophisticated infusion fluid monitoring tools so that the therapy process is smooth, safe, and comfortable. Internet-based technology of things to monitor intravenous chemotherapy drug infusion fluids more accurately and easily. Non-systematic review literature, using online data base: Elsevier (ScienceDirect), IEEE Xplore, ProQuest, Sage Journal with keywords: